2005
DOI: 10.1021/bi047912o
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Substrate Specificity of Haloalkane Dehalogenase LinB from Sphingomonas paucimobilis UT26

Abstract: Haloalkane dehalogenases are microbial enzymes that cleave a carbon-halogen bond in halogenated compounds. The haloalkane dehalogenase LinB, isolated from Sphingomonas paucimobilis UT26, is a broad-specificity enzyme. Fifty-five halogenated aliphatic and cyclic hydrocarbons were tested for dehalogenation with the LinB enzyme. The compounds for testing were systematically selected using a statistical experimental design. Steady-state kinetic constants K(m) and k(cat) were determined for 25 substrates that showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 36 publications
6
59
1
Order By: Relevance
“…A close analysis revealed that the LinB enzymes of Spϩ and UT26 differ from each other by three amino acids and that LinB of B90A differs from those of Spϩ and UT26 by six and seven amino acids residues, respectively. These differences in amino acids are outside the putative catalytic domain (D-108, H-272, and E-132) (7,11,17,18,22,27,28,33,34,37,40,47), but they seem to play an important role in the substrate specificity of the enzymes. Although the studies with purified LinB proteins from B90A and Spϩ are preliminary, they strongly indicate that strain B90A is best suited for biodegradation of ␤-HCH, the most recalcitrant isomer.…”
Section: Discussionmentioning
confidence: 99%
“…A close analysis revealed that the LinB enzymes of Spϩ and UT26 differ from each other by three amino acids and that LinB of B90A differs from those of Spϩ and UT26 by six and seven amino acids residues, respectively. These differences in amino acids are outside the putative catalytic domain (D-108, H-272, and E-132) (7,11,17,18,22,27,28,33,34,37,40,47), but they seem to play an important role in the substrate specificity of the enzymes. Although the studies with purified LinB proteins from B90A and Spϩ are preliminary, they strongly indicate that strain B90A is best suited for biodegradation of ␤-HCH, the most recalcitrant isomer.…”
Section: Discussionmentioning
confidence: 99%
“…The major catalytic domain of LinB belongs to the large and well-characterized ␣/␤-hydrolase fold superfamily of proteins, which characteristically carry out two-step hydrolytic reactions driven by a nucleophile (Asp) that is part of a catalytic triad and using an oxanion hole to stabilize the intermediate (69,114,117). LinB has been the subject of several crystallographic (92,123,166) and computational studies (32,33,69,122,130).…”
Section: Linb Haloalkane Dehalogenase Biochemistrymentioning
confidence: 99%
“…LinB is an enzyme involved in a biochemical pathway for the degradation of the pesticide lindane (␥-hexachlorocyclohexane), where it catalyzes the conversion of 1,3,4,6-tetrachloro-1,4-cyclohexadiene to 2,4,5-trichloro-2,5-cyclohexadiene-1-ol (16). A wide spectrum of haloalkanes can be converted by LinB; however, TCP was estimated to be a haloalkane that did not serve as a substrate for LinB when conventional analytical methods were used (6,12). We decided to apply X-ray crystallography to determine the LinB-TCP complex structure and reveal the structural basis for inactivity.…”
mentioning
confidence: 99%